2017
DOI: 10.5152/tao.2017.2518
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nasal Functions on the Integrity of Grafts after Myringoplasty

Abstract: Objective: We aimed to evaluate the effects of nasal functions for the integrity of grafts after myringoplasty. Methods:In our study 78 patients who underwent myringoplasty operation between 2011-2013 were included. Group I was defined as the group with an intact tympanic membrane following surgery. Group II was defined as the group with a tympanic membrane perforation following surgery. Group I consisted of 44 and Group II consisted of 34 patients. Subjective and objective measurements of nasal functions, Eus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Becker et al [ 13 ] reported that most ET functions had not returned to normal following adento-tonsillectomy in children. In addition, rhinoplasty did not improve the function of the ET or the outcome of myringoplasty [ 7 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Becker et al [ 13 ] reported that most ET functions had not returned to normal following adento-tonsillectomy in children. In addition, rhinoplasty did not improve the function of the ET or the outcome of myringoplasty [ 7 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%